Complete genome sequence of Cellulophaga lytica type strain (LIM-21T). Issue 2 (March 2011) - Pati, Amrita; Abt, Birte; Teshima, Hazuki; Nolan, Matt; Lapidus, Alla; Lucas, Susan; Hammon, Nancy; Deshpande, Shweta; Cheng, Jan-Fang; Tapia, Roxane; Han, Cliff; Goodwin, Lynne; et al.
Abstract Cellulophaga lytica (Lewin 1969) Johansenet al. 1999 is the type species of the genusCellulophaga which belongs to the familyFlavobacteriaceae within the phylum 'Bacteroidetes ' and was isolated from marine beach mud in Limon, Costa Rica. The species is of biotechnological interest because its members produce a wide range of extracellular enzymes capable of degrading proteins and polysaccharides. After the genome sequence ofCellulophaga algicola this is the second completed genome sequence of a member of the genusCellulophaga . The 3, 765, 936 bp long genome with its 3, 303 protein-coding and 55 RNA genes consists of one circular chromosome and is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.